An experimental and numerical investigation of a grid composite cylindrical shell subjected to transverse loading - Arashmehr, Jafar (Strojniški vestnik, 2013)
This paper presents an experimental and numerical study of a stiffened composite cylindrical shell with clamped-free boundary condition under transverse end loading. Electrical strain gauges were employed to measure the strains. Likewise a finite element analysis has been used to validate the experimental results. The finite element method (FEM) software used was ANSYS11. Fairly good agreements were observed between the numerical and the measured results. In addition, a comparison between the stiffened and unstiffened composite shell was carried out. It was found that the intersection of two stiffeners has an important effect in reducing Von Mises stress in the shell. Failure analysis based on TsaiWu failure theory was also performed. It was concluded that stiffening of the shell by helical stiffeners increases the load capacity considerably.
Keywords: analiza napetosti; analiza odpovedi; analiza po metodi končnih elementov; finite element analysis; grid composite structures; kompozitne konstrukcije; merjenje deformacij; stress analysis; transverse loading; transverzalne obremenitve